2016
DOI: 10.1016/j.envpol.2016.09.046
|View full text |Cite
|
Sign up to set email alerts
|

Relative importance of microplastics as a pathway for the transfer of hydrophobic organic chemicals to marine life

Abstract: It has been hypothesised that, if ingested, plastic debris could act as vector for the transfer of chemical contaminants from seawater to organisms, yet modelling suggest that, in the natural environment, chemical transfer would be negligible compared to other routes of uptake. However, to date, the models have not incorporated consideration of the role of gut surfactants, or the influence of pH or temperature on desorption, whilst experimental work has shown that these factors can enhance desorption of sorbed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
212
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 378 publications
(222 citation statements)
references
References 49 publications
7
212
0
3
Order By: Relevance
“…In the case of the latter, MPs have shown the ability to sorb persistent organic pollutants (POPs)45 and subsequently desorb them under simulated gut conditions46. However, recent studies have argued the lower importance of MPs as a vector for translocation of POPs to aquatic biota as compared to other routes like food and water1516. Despite a potentially high concentration of POPs and other contaminants in MPs, the combination of their small particle size and low prevalence indicate that the consumption of sea salt does not appear to be a major route for the contaminant transfer into the human body as compared to other sources like water and food.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of the latter, MPs have shown the ability to sorb persistent organic pollutants (POPs)45 and subsequently desorb them under simulated gut conditions46. However, recent studies have argued the lower importance of MPs as a vector for translocation of POPs to aquatic biota as compared to other routes like food and water1516. Despite a potentially high concentration of POPs and other contaminants in MPs, the combination of their small particle size and low prevalence indicate that the consumption of sea salt does not appear to be a major route for the contaminant transfer into the human body as compared to other sources like water and food.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, top European shellfish consumers are expected to ingest up to 11,000 plastic particles per annum14. Microplastics might be of health concern since they have been shown to carry hazardous chemicals1516 and microorganisms17.…”
mentioning
confidence: 99%
“…Subsequently, these chemicals may desorb from the particles into the body of organisms upon ingestion 55 . However, recent studies have shown the intake of POPs by aquatic organisms from water and food exceeded the potential transfer of POPs from ingested MPs 56, 57 . According to the results of this study, the undetectable level of toxic heavy metals on the isolated particles does not support their potential toxicity and the mechanisms whereby MPs cause toxicity are still unclear.…”
Section: Discussionmentioning
confidence: 99%
“…A few laboratory studies have revealed that organisms may gain hydrophobic additives such as brominated flame retardants by ingesting plastic particles (e.g., Chua et al 2014;Wardrop et al 2016), whereas modeling studies suggested that the additional uptake via the ingestion of plastic particles would be minimal (Gouin et al 2011;Bakir et al 2016). For nonadditives, plastics are not likely to play important roles because fugacity in plastic particles cannot be greater than that in water.…”
Section: Roles Of Plastic Particles On Dynamic Transport Processes Ofmentioning
confidence: 99%
“…However, the observed effects in test organisms would not be environmentally relevant because the dose of plastic particles in laboratory tests is extremely greater than in the field conditions of 100 to 1000 g/km 2 , even in the inner accumulation zones of the ocean gyres (C ozar et al 2014). Modeling studies have revealed that for aquatic organisms, fractional intake via the ingestion of plastic particles would be much smaller than other direct and dietary uptake routes (Gouin et al 2011;Bakir et al 2016). Another aspect that needs to be considered is the direction of chemical flows due to the difference in chemical potential.…”
Section: Introductionmentioning
confidence: 99%